The Effect of Communication Intensity on Relationship Satisfaction in Long Distance Couples - Budi, Fitri Sulistyo; Wicaksono, Awang Setiawan (World Psychology, 2025)
This study aims to analyze the effect of communication intensity on relationship satisfaction among couples in long-distance relationships. The sample consisted of 184 respondents aged 18 to 25 years at the University of Muhammadiyah Gresik. According to Santrock, the age range of 18-25 is considered early adulthood, which is marked by identity exploration, transition to independence, and the development of deeper interpersonal relationships. This study used a quantitative approach with a simple linear regression design. The results of the analysis showed a strong significant relationship between communication intensity and relationship satisfaction, with a significant correlation value of 0.896 (p < 0.01). Reliability testing showed good consistency, with Cronbach's Alpha of 0.870 for communication intensity and 0.878 for relationship satisfaction. ANOVA analysis showed significant differences between respondent groups (F = 18.0, p < 0.001). Hypothesis testing revealed that communication intensity had a significant effect on relationship satisfaction (F = 18.0, p < 0.001), with an R² value of 0.32, indicating that 32% of the variation in relationship satisfaction can be explained by communication intensity. This finding supports the interpersonal communication theory, which emphasizes the importance of effective communication in building healthy relationships. This study provides valuable insights for couples in long-distance relationships, confirming that increasing communication intensity can contribute positively to relationship satisfaction.